1977
DOI: 10.1159/000119661
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Clinical Follow-up of Shunted Hydrocephalic Children

Abstract: In a survey of 29 hydrocephalic children treated by ventriculoatrial shunt (Holter valve) with a follow-up of 4 years, EEG records before the operation and at least once a year thereafter, the authors can support the view that an epileptogenic focus has developed around the place of insertion of the ventricular catheter in 19 cases, leading to epileptic seizures in 17 up to now. Thus the incidence of convulsions in this particular group of patients is 0.59 (17/29), the limits of confidence 95% being 0.39–0.76.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
2
10
2
Order By: Relevance
“…While postshunt seizures are not related to hydrocephalus etiology, it might be possible to prevent them; preshunt seizures are related to the etiology and difficult to be prevented. Although age at shunting was not a significant factor in some studies [1,3,4,20,21,25], others, like our study, showed that shunt at a younger age is a risk factor of developing seizures in shunted patients [7,8]. …”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…While postshunt seizures are not related to hydrocephalus etiology, it might be possible to prevent them; preshunt seizures are related to the etiology and difficult to be prevented. Although age at shunting was not a significant factor in some studies [1,3,4,20,21,25], others, like our study, showed that shunt at a younger age is a risk factor of developing seizures in shunted patients [7,8]. …”
Section: Discussioncontrasting
confidence: 58%
“…Thus, it is important to identify the risk factors of seizure disorders in shunted hydrocephalus which helps us to prevent the seizures and associated problems. Birth injuries, etiology of hydrocephalus, age at initial shunt placement, associated shunt malfunctions and infections, high number of shunt revisions, concomitant pathology, and presence of special types of central nervous system malformations are considered to be risk factors of seizures in shunted hydrocephalus [1,2,5,8]. However, there are lots of discrepancies among different studies about the role and importance of each risk factor [2].…”
Section: Introductionmentioning
confidence: 99%
“…Graebner and Celesia [9] stated that 62% of subjects in the nonshunted group and 85% in the shunted group had abnormal EEGs, and focal specific paroxysmal discharges were present in 38% in the shunted group, in contrast to only 10% in the nonshunted group. Comparing EEG recordings taken before and after shunt surgery, Varfis et al [24] supported the view that an epileptogenic focus has developed around the place of ventricular catheter of the shunt system. Among shunted hydrocephalic patients after meningitis or intraventricular hemorrhage fits other than generalized convulsions were rare, while generalized and focal fits were equally represented in the hydrocephalic patients after Chiari malformation or aqueduct stances [22].…”
Section: Discussionmentioning
confidence: 93%
“…many others [17,24,23] that there is an increased risk of seizures in patients with CNS malformations, while only Copeland et al [6] were not able to convince their readers that there was a correlation between pathologic conditions causing hydrocephalus and the incidence of seizures. Mental retardation is another factor that aggravates the risk of having or developing seizures.…”
Section: Discussionmentioning
confidence: 99%
“…[1718] Brainstem auditory evoked potentials, when serially performed, help in identifying the structural abnormalities of brainstem and can also be an earlier indicator of shunt malfunction [Tables 1 and 2]. [1921]…”
Section: Historymentioning
confidence: 99%